Conservation interventions to reduce vessel strikes on sea turtles: A case study in Florida. (June 2021) - Fuentes, Mariana M.P.B.; Meletis, Zoë A.; Wildermann, Natalie E.; Ware, Matthew
Abstract: Sea turtles and boating activities often occur in shared waters. This is problematic because sea turtles are susceptible to vessel strikes since they spend significant portions of their lives in nearshore shallow water to breathe, reproduce, and feed. Targeted conservation strategies are needed to reduce vessel strikes on sea turtles, and successful integration of stakeholder perspectives is necessary for conservation success. Here, we present results from a multi-step approach to investigate responses to potential conservation interventions for reducing vessel strikes on sea turtles. First, challenges and opportunities related to potential interventions that could be used to reduce sea turtle vessel strikes were discussed and assessed by a workshop of conservation and enforcement experts. Second, the workshop-identified interventions were incorporated into a survey questionnaire for recreational boaters. Third, this face-to-face survey was administered around the St. Lucie Inlet, an area identified as a vessel strike "hot spot" in Florida (USA). The questionnaire asked about boating preferences and practices, existing and potential conservation interventions, and sea turtle presence in the area. Respondents suggested that greater community support for implementation of interventions would be obtained if they (1) were voluntary rather than mandatory/legislated, (2) overlapped with existing interventions (e.g., if speed mitigation zones for sea turtles overlapped significantly with existing speed reduction zones for manatees) and/or added minimal new restrictions and inconveniences, and (3) were accompanied by explanatory materials on the need for, and the effectiveness of, such management strategies. Boater buy-in for management strategies and compliance can vary significantly. As such, our exploratory study should be replicated where proposed sea turtle conservation-related strategies might be warranted to ensure proper contextual fit. Boaters are a powerful, integral, and a growing demographic that must be effectively and respectfully engaged for effective sea turtle conservation in Florida and beyond. Highlights: Minimizing vessel-related mortality of sea turtles is a priority. Boater perspectives on strategies to reduce vessel strikes were solicited. The willingness of recreational boaters to reduce vessel strikes was explored. Go-slow zones were among the most acceptable types of boating-related interventions. Any intervention implemented must be accompanied by boater education.